Estudo dos efeitos da adição de chumbo e bismuto nas propriedades dielétricas da matriz cerâmica BiNbO4 e suas aplicações em rádio frequência e antenas. - Almeida, José Silva de (2011)
In this work, the structural and dielectric properties of triclinic phase (β) BiNbO4with oxide additions (BNO:Y, Y=0,3,5,10 wt.% of PbO, Bi2O3) were investigated as a function of the frequency and temperature for use as dielectric resonators and applications in RF and microwaves devices. Our interest is to obtain dielectric ceramics with a high dielectric permittivity combined with low dielectric losses and thermal stability. In the measurements accomplished at room temperature (25°C) we obtained a high value of dielectric permittivity for BNO5Pb (5% of PbO) with value of ε’ r= 78.44 at 100kHz and a low value of loss tangent for BNO3Pb (3wt.% of PbO) with tan = 2.19 x 10-4 at 33,69MHz. For the temperature varying and a fixed frequency of 100 kHz, we obtained a high value of dielectric permittivity to ε’r=76.4 at 200°C with BNO5Pb and a low value of dielectric loss at 80°C to BNO3Bi (3wt.% of Bi2O3) with a value of tanδ= 5.4 x 10 -3. The measurements temperature coefficient of capacitance (TCC) showed that the thermal capacitive stability can be reached, at 1MHz by increasing the addition level of Bi or Pb up to TCC=0ppm/°C. With BNO we have obtained a TCC=-55.06 ppm/°C that doped with 3% of Bi moved up for TCC=+86.74 ppm/°C and doped with 3% of Pb it passed to TCC=+208.87 ppm/°C. The measurements in the microwave range of 4-6 GHz were obtained using the HakkiColeman method. For the BNO, sintering at 1025°C for 3h, we obtained a product of quality factor for the resonance frequency (Qxf) equal to 1470.75 GHz and a dielectric permittivity (ε’r) equal to 31.38. In this study we obtained a ceramic BNO useful for the development of ceramic capacitors, radio-frequency device, microwave devices and dielectric resonator developments.